The Didactic Aspect of the Problem of the Theory of Means of Study in the Pedagogical Investigations - Olga Skal’s’ka (Pedagogical Discourse, 2012)
The basic results of studying the problem of the theory of means of study are analysed in the article. It amplified the definitions of notions – basic means of study, additional means of study, subsidiary means of study. The scientist’s point of view as to classification and systematization of the means of study is generalized. The attention is made to the problem of creating the system of means of study in the process of foreign language teaching.